Correlation Glucose, Uric Acid, and Cholesterol Levels Towards Health Conditions in the Highlands: POCT Approach - Arifa Mustika; Yetti Hernaningsih; Puspa Wardhani; Siti Khaerunnisa; Nastasya Nunki; Baiq Nasha Islaeli; Uli Mas'uliyah Indarwati; Musholli Himmatun Nabilah; Teguh Satrio; Alfino Validita Sidiq; Fita Triastuti; Mochammad Reza Desianto; Agil Saputra; Novi Ersanto; Widaninggar Rahma Putri; Desty Indah Sari (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Degenerative diseases arise when age increases due to the weakening of the body's physiological condition. The purpose of this study was to measure glucose, uric acid, and cholesterol levels in residents of Segunung Village to improve lifestyles and quality of life. As many as 110 residents of Segunung Village were used as subjects in this cross-sectional study. Glucose, uric acid, and cholesterol levels were measured using Point of Care Testing (POCT). A cut-off value of <200 was used to define high cholesterol levels. Only cholesterol levels showed an increase when compared with reference values, while glucose and uric acid levels were normal. Interestingly glucose was significantly correlated with age (r=0.309, p=0.001). The approach using POCT describes the overall condition of Segunung villagers and can be used as a basis for glucose, uric acid, and cholesterol screening tests.